2020
DOI: 10.1093/infdis/jiaa048
|View full text |Cite
|
Sign up to set email alerts
|

Human Immunodeficiency Virus (HIV)-Negative Men Who Have Sex With Men Have Higher CD8+ T-Cell Counts and Lower CD4+/CD8+ T-Cell Ratios Compared With HIV-Negative Heterosexual Men

Abstract: Background We previously reported T-cell senescence to be similar in people with human immunodeficiency virus (PWH) with suppressed viremia (predominantly men who have sex with men [MSM]) and human immunodeficiency virus (HIV)-negative otherwise comparable controls but greater than in healthy blood donors. This led us to compare CD4+ and CD8+ T-cell counts and CD4+/CD8+ ratios between HIV-negative MSM and men who only have sex with women (MSW) and relate observed differences in behavioral fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Another plausible contributor to the CD8 T-lymphocyte count differences we observed is that syphilis may be a proxy for other unmeasured concomitant STIs which are more directly linked to elevation of CD8 T-lymphocyte level. For instance, MSM showed higher CD8 T-lymphocyte levels and lower CD4/CD8 ratios than men who only have sex with women in a study of 368 HIV-negative participants, in which the differences could be partially explained by the higher CMV seroprevalence among MSM [37].…”
Section: Discussionmentioning
confidence: 99%
“…Another plausible contributor to the CD8 T-lymphocyte count differences we observed is that syphilis may be a proxy for other unmeasured concomitant STIs which are more directly linked to elevation of CD8 T-lymphocyte level. For instance, MSM showed higher CD8 T-lymphocyte levels and lower CD4/CD8 ratios than men who only have sex with women in a study of 368 HIV-negative participants, in which the differences could be partially explained by the higher CMV seroprevalence among MSM [37].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study comparing MSM and heterosexual men, all of whom were HIV-negative, found MSM and MSM reporting multiple recent partners more specifically to have lower CD4/CD8 ratios on average. Cytomegalovirus (CMV) infection was hypothesized to contribute to observed differences, but drug use did not appear to be associated [ 24 ]. Unfortunately, we were not able to account for CMV infection in our analysis due to data reliability concerns.…”
Section: Discussionmentioning
confidence: 99%
“…These diseases have been correlated with a decrease in CD4+/CD8+ ratio and an increase in CD8+ lymphocytes (Freeman et al, 2016 ; Pope et al, 1994 ; Strindhall et al, 2013 ; Vieira et al, 2017 ). The results of various studies in this regard have been conflicting, with some associating a decrease in this ratio in HIV‐positive patients with greater morbidity and mortality (Ferguson et al, 1995 ; Verboeket et al, 2020 ; Wikby et al, 1998 )) and others reporting no correlation between the two (McBride & Striker, 2017 ).…”
Section: Discussionmentioning
confidence: 99%